CARRIAGE OF MULTIDRUG RESISTANT ENTEROCOCCUS FAECIUM AND ENTEROCOCCUS FAECALIS AMONG APPARENTLY HEALTHY HUMANS - Adesida, Solayide A.; Ezenta, Cynthia C.; Adagbada, Ajoke O.; Aladesokan, Amudat A.; Coker, Akitoye O. (African Journal of Infectious Diseases (AJID), 2017)
Enterococci are indigenous flora of the gastro-intestinal tracts of animals and humans. The recent years have witnessed increased interest in two major species, E. faecium and E. faecalis, because of their ability to cause serious infections and their intrinsic resistance to antimicrobials. In this study, human faecal samples were processed to determine the frequency of occurrence of E. faecium and E. faecalis and evaluate the susceptibility of the isolates to antibiotics. One hundred faecal samples were collected from apparently healthy individuals and 73 Enterococcus were phenotypically identified using conventional methods. The susceptibility profiles of the isolates to 9 different antibiotics were determined using disk diffusion method and the results were interpreted according to Clinical and Laboratory Standards Institute (CLSI) guidelines. Sixty-five isolates were differentiated into 36 (55.4%) E. faecium and 29 (44.6%) E. faecalis. No dual colonization by the two species was observed and isolation rate was independent of sex. Antimicrobial susceptibility testing revealed high occurrence of several different combinations of resistant patterns. The 65 isolates were resistant to ceftriaxone, cefuroxime and ceftizoxime. Enterococcus faecium exhibited resistance to erythromycin (88.9%), gentamicin (77.8%), amoxicillin-clavulanate (63.9%), ofloxacin (44.4%), teicoplanin (19.4%) and vancomycin (16.7%). Enterococcus faecalis showed the least resistance to vancomycin (13.8%) and teicoplanin (27.7%). The high prevalence of resistant strains in this study can be attributed to misuse of drugs. This can be curtailed by stopping the sale of antibiotics across the counter and creating awareness among the populace by Government and Health Agencies on the consequences of unregulated antibiotic use.